Hypovigilance detection using energy of electrocardiogram signals - Arun, S.; Sundaraj, Kenneth, Prof. Madya Dr.; Murugappan, M. (NISCAIR PUBLICATIONS, 2013)
Link to publisher's homepage http://nopr.niscair.res.in/